Tourism Development in Upper Manang Valley of Annapurna Region - Subedi, Bhim P; Chapagain, Prem Sagar (Nepal Tourism and Development Review, 2013)
The Context: People have traveled throughout history as they have moved from one place to another for various reasons. However, as a business and as guided by individual and group’s voluntary activity, it flourished after the second half of the 20th century, especially after the Second World War. Nepal followed a similar pattern as it was opened for outsiders only after 1950. Since then Nepal’s natural beauty within various ecological zones and its rich cultural heritage have attracted large number of tourists annually from around the world and particularly from Western Europe. DOI: http://dx.doi.org/10.3126/ntdr.v1i1.7370 Nepal Tourism and Development Review Vol.1(1) 2011 56-68